2018
DOI: 10.1049/iet-syb.2018.5025
|View full text |Cite
|
Sign up to set email alerts
|

Identifying cancer‐related microRNAs based on subpathways

Abstract: MicroRNAs (miRNAs) are a class of small endogenous non-coding genes that play important roles in posttranscriptional regulation as well as other important biological processes. Accumulating evidence indicated that miRNAs were extensively involved in the pathology of cancer. However, determining which miRNAs are related to a specific cancer is problematic because one miRNA may target multiple genes and one gene may be targeted by multiple miRNAs. The authors proposed a new approach, named miR_SubPath, to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…MiRNAs are a class of endogenous small non-coding genes that primarily exert its effects on post-transcriptional regulation and different biological processes [9]. Abnormally expressed miRNAs play pivotal roles in the development of many human cancers [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are a class of endogenous small non-coding genes that primarily exert its effects on post-transcriptional regulation and different biological processes [9]. Abnormally expressed miRNAs play pivotal roles in the development of many human cancers [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…As the overlapped critical miRNA in three cancers, hsa-mir-21 was reported to involved in various cancers such as colorectal cancer, breast cancer and lung cancer (Xu et al, 2016;Liu W. et al, 2018). It has been reported that overexpression of miR-21 The bold values are the number of interactions with influence strength more than 0.5.…”
Section: Most Of the Critical Mirnas Involve In Some Important Biologmentioning
confidence: 99%
“…The dysfunctions of miRNAs have been reported to be involved in the tumorigenesis of various cancers (Bartel, 2004;Gotte, 2010;Dela Cruz and Matushansky, 2011;Lovat et al, 2011;Liu W. et al, 2018;Xu et al, 2018). For this reason, miRNAs have become potential biomarkers in cancer diagnosis and treatment (Slack and Chinnaiyan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of small endogenous non-coding genes with~22 nucleotides that exert pivotal roles in post-transcriptional regulation and different biological processes, especially in the progression of cancer [11]. MiR-196b-5p is involved in the progression of several cancers, such as colorectal cancer [12], gastric cancer [13,14].…”
mentioning
confidence: 99%